Systemic inflammation and symptomatology in patients with prostate cancer treated with androgen deprivation therapy: Preliminary findings. Issue 9 (30th December 2020) - Hoogland, Aasha I.; Jim, Heather S. L.; Gonzalez, Brian D.; Small, Brent J.; Gilvary, Danielle; Breen, Elizabeth C.; Bower, Julienne E.; Fishman, Mayer; Zachariah, Babu; Jacobsen, Paul B.
Abstract : Background: Increases in fatigue, depressive symptomatology, and cognitive impairment are common after the initiation of androgen deprivation therapy (ADT) for prostate cancer. To date, no studies have examined the potential role of inflammation in the development of these symptoms in ADT recipients. The goal of the current study was to examine circulating markers of inflammation as potential mediators of change in fatigue, depressive symptomatology, and cognitive impairment related to the receipt of ADT. Methods: Patients treated with ADT for prostate cancer (ADT+; n = 47) were assessed around the time of the initiation of ADT and 6 and 12 months later. An age‐ and education‐matched group of men without a history of cancer (CA–; n = 82) was assessed at comparable time points. Fatigue, depressive symptomatology, and cognitive impairment were assessed with the Fatigue Symptom Inventory, the Center for Epidemiological Studies Depression Scale, and a battery of neuropsychological tests, respectively. Circulating markers of inflammation included interleukin 1 receptor antagonist (IL‐1RA), interleukin 6 (IL‐6), soluble tumor necrosis factor receptor II (sTNF‐RII), and C‐reactive protein (CRP). Results: Fatigue, depressive symptomatology, and serum IL‐6 increased significantly over time in the ADT+ group versus the CA– group; rates of cognitive impairment also changed significantly between the groups. No significant changes in IL‐1RA, sTNF‐RII, or CRP over time were detected. Treatment‐related increases in IL‐6 were associated with worsening fatigue but not depressive symptomatology or cognitive impairment. Conclusions: Results of this preliminary study suggest that increases in circulating IL‐6, perhaps due to testosterone inhibition, may play a role in fatigue secondary to receipt of ADT. Additional research is needed to determine whether interventions to reduce circulating inflammation improve fatigue in this population. Abstract : Androgen deprivation therapy is associated with increases over time in fatigue, depressive symptomatology, and circulating interleukin 6. Increases in interleukin 6 over time are associated with worsening treatment‐related fatigue but not depressive symptomatology or cognitive impairment.